Association between executive function and the evolution of behavioral disorders in Alzheimer's disease. (7th July 2020) - Rouch, Isabelle; Padovan, Catherine; Boublay, Nawèle; Pongan, Elodie; Laurent, Bernard; Trombert‐Paviot, Béatrice; Krolak‐Salmon, Pierre; Dorey, Jean‐Michel
Abstract : Objective: This study was aimed at evaluating the association between cognitive functioning and the occurrence of behavioral and psychological symptoms of dementia (BPSD) in patients with Alzheimer's disease (AD). Methods/Design: The population is derived from the PACO cohort, including 237 patients with prodromal or mild AD. A neuropsychological tests battery exploring verbal and visual memory, language, attention, and executive functions was performed at baseline. BPSD were assessed at 6‐, 12‐, and 18‐month follow‐up with neuropsychiatric inventory (NPI). Results: Lower baseline performance on Stroop test interference score was associated with higher subsequent overall NPI scores ( P = .006), subscores of anxiety/depression ( P = .03), and apathy inventory ( P = .01). Conversely, other executive functions, verbal or visual memory, and language performances were not associated with a higher risk of BPSD. Conclusion: Our results suggest that poorer inhibition performance would be associated with a higher risk of 18‐month BPSD occurrence, including anxiety, depression, and apathy. A better knowledge of the predictive factors of the BPSDs would make it possible to better identify the patients at risk, to propose preventive strategies and an earlier adapted care. J Am Geriatr Soc 68:‐, 2020.